A Stranger in the Night: Canadian Assistance to Southeastern Europe (1990-2005) - Asteris Huliaras (European Regional Science Association (ERSA), 2006)
Official Development Assistance to the Balkans in the 1990-2005 period seem to reflect two different and contradictory donor 'geopolitical visions'. Some countries (like Greece and France) tended to consider the Balkans as a homogenized 'aid space'. On the contrary other countries (like Japan) or international organizations (like the European Union) tended to divide the Balkans into two 'aid spaces': the Western and the Eastern Balkans. The second 'geopolitical vision' led to differentiated aid policies. The Balkans were considered as being consisted of two groups of recipients: Western Balkans that received humanitarian and short-term reconstruction aid and Eastern Balkans that received more 'developmental' aid. In the last fifteen years the Balkans were one of the priority regions in Canada's foreign policy. Canada's military involvement in the Kosovo war was the largest military of the country since the Korean War. Also Canada has deployed an average of 1500-2000 peacekeepers at any given time in the Balkans and accepted more than 30.000 refugees from the region. But above all Canada provided hundreds of millions of for the reconstruction of the region. The paper focuses on Canada's bilateral aid to the Balkans, examines Canada's aid motives and attempts to identify the main differences between Canada's aid efforts in the region and those of other OECD countries. Above all the paper analyses Canada's regional geopolitical vision and tries to determine how its adoption influenced aid policy decisions.
Keywords: 330